НЕХВАТКА АРХИТЕКТУРЫ СОЦИАЛЬНОГО - ШИЛЬМАН, М. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
В статье анализируется способность современной архитектуры изобретатьновые конфигурации социального и утверждать их языком радикальных требований, чтопредставляет собой своеобразную политику опустошающего вмешательства впереуплотненную среду общества потребления.Шильман М. БРАК АРХІТЕКТУРИ СОЦІАЛЬНОГО У статті аналізуєтьсяздатність сучасної архітектури винаходити нові конфігурації соціального істверджувати їх мовою радикальних вимог, що є своєрідною політикою спустошуючоговтручання у надщільну середу суспільства споживання.Ключові слова: архітектура, соціальна структура, дизайн, символічний порядок,політика, простір, бачення, образShilman M. THE DEFICIENCY OF ARCHITECTURE OF THE SOCIAL The ability ofnon-classical architecture to invent new social configurations and to assert them by thelanguage of radical requirements is analysed in the article, that is the original politics ofdevastating interference into the hyperdensity environment of society of consumption.The mistrust to great philosophical systems in a context of nonclassical thinking caused asearch of new alternatives to old metaphysics of architecture. Now the philosophy andarchitecture have an intimate contact in matters of diagnostics of modern social space. Thepostmodern condition (as «incomplete project» and «end of social») can be think by analogy tothe Babel tower. This kind of «ruins» and/or «building» is an ambiguous «breakup», whichserves as a field and the base to any future social configurations. Any policy that is carried outin this field is the modulation of parameters and selection of settings of social architecture. Inthe mode of consumer design architecture is a form of mass-media; it mobilizes functionalspaces and simulates non-functional space. Architecture in radical mode is the art of seeing theworld by forms and is focused on demobilization of functional spaces by making non-functionalin the density of the mass society. Only in the second case the architecture generates a newsymbiotic relationship, acting as the creation of a new social constructions.Keywords: architecture, social structure, design, symbolic order, policy, space, vision,image.